Majority Merging by Adaptive Counting - Primiero, Giuseppe; Meheus, Joke (Synthese (KRA Serie), 2008)
The present paper introduces a belief merging procedure by majority using the standard format of Adaptive Logics. The core structure of the logic ADM(c) (Adaptive Doxastic Merging by Counting) consists in the formulation of the conflicts arising from the belief bases of the agents involved in the procedure. A strategy is then defined both semantically and proof-theoretically which selects the consistent contents answering to a majority principle. The results obtained are proven to be equivalent to a standard majority operator for bases with partial support.